Platelet Transfusion in Perioperative Medicine - Thiele, Thomas; Greinacher, Andreas (Seminars in Thrombosis and Hemostasis, 2020)
Platelet transfusions aim to improve primary hemostasis and to prevent or treat bleeding in patients with reduced platelet numbers and/or platelet function. In this review, the authors address the role of platelet transfusions with a focus on perioperative medicine. They summarize different causes of thrombocytopenia in perioperative patients, describe general characteristics and potential adverse effects of different platelet concentrates, describe principles of perioperative platelet transfusion strategies, and highlight specific perioperative scenarios, for example, in patients undergoing antiplatelet therapy. The evidence for any transfusion threshold in perioperative patients based on platelet numbers is low. The evidence supporting prophylactic platelet transfusions in the perioperative setting is very low, and all recommended thresholds for preintervention platelet transfusions are based on weak evidence or expert opinion. Besides the platelet count, platelet function, additional risk factors for bleeding, and the pharmacokinetic properties of concomitant antiplatelet drugs are important criteria for the decision to transfuse or not to transfuse platelets. The few available prospective trials give at least a signal that a liberal platelet transfusion strategy might be associated with poorer outcomes compared with a restrictive platelet transfusion strategy in critically ill patients. Given the unknown risks for adverse outcomes, a therapeutic transfusion strategy during surgery (eventually guided by point of care testing in cardiac surgery, major liver surgery, and major trauma) may be most appropriate for interventions, in which intraoperative bleeding can be controlled until platelets are available, and during the postsurgery period.
Keywords: platelet; perioperative; transfusion; thrombocytopenia; antiplatelet therapy